2013
DOI: 10.1016/j.hrthm.2013.01.029
|View full text |Cite
|
Sign up to set email alerts
|

Low-level vagus nerve stimulation upregulates small conductance calcium-activated potassium channels in the stellate ganglion

Abstract: Background Small conductance calcium activated potassium (SK) channels are responsible for afterhyperpolarization that suppresses nerve discharges. Objectives To test the hypotheses that low-level vagus nerve stimulation (LL-VNS) leads to the upregulation of SK2 proteins in the LSG. Methods Six dogs (Group 1) underwent 1-wk LL-VNS of the left cervical vagus nerve. Five normal dogs (Group 2) were used as control. SK2 protein levels were examined by western blotting. The ratio between SK2 and glyceraldehydes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 27 publications
1
44
0
Order By: Relevance
“…A subsequent study by the same group showed that in the LSG, LL-VNS also resulted in the upregulation of small-conductance calcium-activated potassium channel type 2 and increased its expression in the cell membrane ( Figure 8B and 8C). 155 These changes may facilitate hyperpolarization of the ganglion cells and reduce the frequency of neuronal discharges. 156 Thus, LL-VNS can functionally and structurally remodel the LSG, which might explain some of its antiarrhythmic effects.…”
Section: Neural Stimulationmentioning
confidence: 99%
See 1 more Smart Citation
“…A subsequent study by the same group showed that in the LSG, LL-VNS also resulted in the upregulation of small-conductance calcium-activated potassium channel type 2 and increased its expression in the cell membrane ( Figure 8B and 8C). 155 These changes may facilitate hyperpolarization of the ganglion cells and reduce the frequency of neuronal discharges. 156 Thus, LL-VNS can functionally and structurally remodel the LSG, which might explain some of its antiarrhythmic effects.…”
Section: Neural Stimulationmentioning
confidence: 99%
“…25,26 It causes histological remodeling of the LSG that in turns decreases the sympathetic outflow to the heart. 30,155 Additionally, VNS leads to a reduction of heart rate, which may be protective because this may attenuate ratedependent alterations in ventricular action potential duration, refractoriness, and dispersion of both factors. However, the anti-VF effect of VNS is reduced but not abolished during constant cardiac pacing, 34,179 suggesting that the decrease in heart rate is an important but not the only protective mechanism.…”
Section: Neural Stimulationmentioning
confidence: 99%
“…17, 87 It is of interest that vagal stimulation, which is being evaluated as a treatment for HF to prevent sudden death, leads to cholinergic transdifferentiation of stellate ganglion in dogs. 88 …”
Section: Pathophysiologymentioning
confidence: 99%
“…Shen et al (Shen et al, 2011) demonstrated that low-level vagus nerve stimulation reduced cardiac stellate ganglion activity and paroxysmal AF. The mechanism of the reduced stellate ganglion activity might be attributable in part to the upregulation of SK2 channels in the stellate ganglion (Shen et al, 2013). …”
Section: Differential Expression Of Sk Channels In Normal and Diseasementioning
confidence: 99%